2005
DOI: 10.1507/endocrj.52.353
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plasma Brain Natriuretic Peptide Level in Patients with Type 2 Diabetes

Abstract: Abstract. This study investigates whether the plasma brain natriuretic peptide (BNP) level is increased by the clinical traits of diabetes, including its complications, and whether these levels are affected by the presence of other combined diseases such as hypertension, hyperlipidemia, and coronary heart disease (CHD) in patients with diabetes. In 223 patients with Type 2 diabetes, the mean value of plasma BNP reached 32.3 ± 4.1 pg/mL. The levels significantly increased with age, hypertension, and CHD but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 38 publications
1
22
0
6
Order By: Relevance
“…A positive association between BNP level and UACR was found in a Japanese study of 316 patients with type 2 diabetes mellitus [6]. In a Japanese study of 233 patients with type 2 diabetes mellitus, BNP level was positively associated with macroalbuminuria [7]. These findings are in partial agreement with our results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A positive association between BNP level and UACR was found in a Japanese study of 316 patients with type 2 diabetes mellitus [6]. In a Japanese study of 233 patients with type 2 diabetes mellitus, BNP level was positively associated with macroalbuminuria [7]. These findings are in partial agreement with our results.…”
Section: Discussionsupporting
confidence: 91%
“…In previous epidemiological studies regarding the association BNP and renal function, plasma BNP ranged from 10.8 to 46.3 ng/dL [5][6][7][8][9]. The discrepancies among these studies may be explained, at least in part, by differences in sample size; the definition of renal function; characteristics such as age, sex, race, BMI, prevalence of coronary heart diseases, subclinical heart failure and hypertension; and other confounding factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11,12 However, those studies and current study data included patients with coronary heart disease (CHD). Recently, Igarashi et al 13 reported similar results for type 2 diabetic patients, but they observed no difference between patients with normoalbuminuria and those with microalbuminuria/ macroalbuminuria after excluding patients with CHD. Thus, in this study, multiple regression analysis was performed after excluding patients with CHD and cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 86%
“…The values of FPG and IRI were also used to estimate the homeostasis model assessment insulin resistance (HOMA-IR) index 14) . In addition, compliance with the agent, including clinically adverse side-effects, was carefully checked, and the following parameters were measured each month: glutamic oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), and lactate dehydrogenase (LDH) for hepatic dysfunction 10) ; and plasma brain natriuretic peptide (BNP) for fluid retention, peripheral edema, and congestive heart failure 15) . Furthermore, to evaluate the occurrence of edema by the agent, the edema index was measured using a body composition analyzer, InBody 3.0 ® (Biospace, Tokyo, Japan), at the beginning (Month 0) and end (Month 4) of the study.…”
Section: Protocol and Measurement Of Laboratory Parametersmentioning
confidence: 99%